1984
DOI: 10.1159/000118065
|View full text |Cite
|
Sign up to set email alerts
|

Drugs as Research Tools in Psychology: Cholinergic Drugs and Information Processing

Abstract: It is argued that cholinergic drugs have an effect on both attentional and memory aspects of information processing. This thesis is supported by studies with anticholinesterases, cholinolytics, and nicotine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Scopolamine-or lorazepam-induced sedation (rated by the subject or measured by motor retardation) was found to be more closely related to performance on attention and psychomotor tasks than to performance on memory tasks [5]. In some studies, cholinergic drugs have been shown to have an effect on both attentional and memory aspects of information processing [14].…”
Section: Introductionmentioning
confidence: 99%
“…Scopolamine-or lorazepam-induced sedation (rated by the subject or measured by motor retardation) was found to be more closely related to performance on attention and psychomotor tasks than to performance on memory tasks [5]. In some studies, cholinergic drugs have been shown to have an effect on both attentional and memory aspects of information processing [14].…”
Section: Introductionmentioning
confidence: 99%
“…In our work, our strategy has been to use drugs as tools for analyzing the neurochemical mechanisms underlying information processing [1], In developing this approach, we have used experimental paradigms, which have been developed from attentional capacity models of informa tion processing [2], These theoretical models have moved away from structural limitations to process models, em phasizing instead the importance of effective and efficient strategies for processing, including the encoding and re trieval of information. Within this context, a crucial role is played by the supervisory control mechanism which coordinates the necessary operations.…”
Section: Introductionmentioning
confidence: 99%
“…Transdermal scopolamine has been dem onstrated to provide significant protection against mo tion sickness, both under laboratory conditions of con trolled motion [Graybiel et al, 1976[Graybiel et al, , 1982, and at sea [Price et al, 1981;Van Marion et al, 1985], Current models of motion sickness place primary emphasis upon muscarinic acetylcholine neurotransmis sion, which is hypothesised to underly the transmission of motion information from the vestibular organs, to the brainstem areas subserving vomiting Reason and Brand, 1975]. Acetylcholine is also important for psychological functions such as sustained attention, vigilance, stimulus processing, and memory storage [Deutsch, 1971;Warburton, 1975;Warburton and Wesnes, 1984]; these functions are significantly im paired by oral or parenteral scopolamine [Colquohoun et al, 1962; Ghoneim and Mewaldt, 1975;Lukomskya and Nikolskay, 1971;Parrott, 1986; Peterson, 1977; Warburton. 1983, 1984).…”
mentioning
confidence: 99%